ChemInform Abstract: Fluorination of α, β‐Unsaturated Carbonyl Compounds Using Elemental Fluorine. Issue 21 (6th May 2016) - Vints, Inna; Rozen, Shlomo
Abstract: In contrast to other halogens, the addition of fluorine to alkenes occurs as a syn addition.